Uji Kelayakan Media Audiovisual untuk Promosi Kesehatan Personal Hygiene Genital pada Siswa Berkebutuhan Khusus di Sekolah Inklusi SMA Muhammadiyah 6 Surakarta - Mulyani Adi Astutiatmaja; Ayu Khoirotul Umaroh (Universitas Respati Indonesia, 2025)
Reproductive health issues are still considered a taboo topic in Indonesia, including among children with special needs. One of the basic health needs for children with special needs is the ability to clean themselves, including their genitalia, which is referred to as personal hygiene. Information regarding reproductive organ health can be delivered through health promotion. Audiovisual media can be used as an alternative to provide health education to children with special needs because video media is very easy to understand. The aim of this study is to test the feasibility of audiovisual media as a health promotion tool for personal hygiene and genital care for children with special needs at the SMA Muhammadiyah 6 Surakarta inclusive school. This study applied the Research and Development (R&D) method, which includes problem identification and needs analysis, reference material collection, product design, design validation, design revision, small group trials, and product revision. The informants in this study were selected using purposive sampling techniques, which consisted of two media experts, one subject matter expert, and six children with special needs for the small group trial. The results of this study are audiovisual media in the form of a video containing material about the importance of maintaining reproductive organ health. The results of the validity tests conducted by the first media expert showed an average score of 4.6, categorized as good; the second media expert scored 4.12, also in the good category; the subject matter expert scored 4.87, in the good category; and the small group respondents scored 4.44, which is categorized as good. Based on the validation results from the media experts, subject matter expert, and small group respondents, the audiovisual media on genital hygiene is categorized as good and considered suitable for use as a health promotion tool for children with special needs at SMA Muhammadiyah 6 Surakarta inclusive school.